Sistem penilaian prestasi pelajar - Hasan Basari, Abd. Samad (2002)
The explosion of information technology has tremendously helped students in their search for knowledge without depending on their teachers or reference books. Various methods have been adopted to enable students understand concepts taught. Up till now the method used mainly focus on explanation of concepts presented by teachers and students attempt to understand them. Until today studies to measure the level of students' understanding have not much been carried out. The purpose of this project is to study the feasibility of using computer technology in the measurement of the level of students' understanding and to develop its software. The software will utilize the approach of artificial intelligence in the process of testing and evaluating their level of understanding. The project will produce a prototype system of evaluating students' performance based on test questions. By using the software teachers who do not have the expertise in computer technology will be able to construct test question easily and fast. They will be able to upload lecture notes, and analyze the result, test the application of the module before using it on the internet. For the students, the system will enable them to work on their own, to take quiz via the internet, to examine the syllabus and to view their performance from time to time. The software is also installed with a communication device to enable students to interact with their teacher to overcome problems frequently faced in the software system via the internet.